Nickel(ii)dibenzotetramethyltetraaza[14]annulene complex immobilized on amino-functionalized TUD-1: an efficient catalyst for immediate and quantitative epoxidation of cyclohexene under ambient conditions. (14th November 2020) - Abboud, Mohamed; Sahlabji, Taher; Eissa, Murad; Bel-Hadj-Tahar, Radhouane; Mubarak, Ahmed T.; Al-Zaqri, Nabil; Hamdy, Mohamed S.
Abstract : Nickel(ii )dibenzotetramethyltetraaza[14]annulene complex immobilized on amino-functionalized TUD-1 as a new nanocatalyst for spontaneous and quantitative epoxidation of cyclohexene under ambient conditions. Abstract : A nickel(ii )dibenzotetramethyltetraaza[14]annulene complex (Nitmtaa) is prepared and immobilized on amino-functionalized TUD-1 (N-TUD-1) via a Ni–N (NH2 ) bond to obtain a stable and reusable new nanocatalyst named as Nitmtaa@N-TUD-1. The catalytic activity performance of this new nanocatalyst was evaluated in the epoxidation of cyclohexene under ambient conditions (25 °C, 1 atm) using meta -chloroperoxybenzoic acid ( m -CPBA) as the oxidant, and CH2 Cl2 /CH3 CN (1 : 1 v/v) as the solvent. (3-Aminopropyl)triethoxysilane (APTES) was first grafted on the TUD-1 surface, then Nitmtaa was added and coordinated with amine groups on the TUD-1 surface to produce the nanocatalyst Nitmtaa@N-TUD-1. The structure and morphology of the obtained nanocatalyst were studied using SEM, HR-TEM, BET analysis, FTIR spectroscopy, and powder XRD analysis. The thermal stability was investigated using TGA and DTA. HR-TEM and XRD results revealed a high dispersion of Nitmtaa on the TUD-1 surface. The obtained nanocatalyst exhibited an immediate and quantitative epoxidation reaction of cyclohexene to cyclohexene oxide under ambient conditions with a high turnover frequency (TOF) of ∼42.11 s −1 . Moreover, the catalyst Nitmtaa@N-TUD-1 maintained the high catalytic activity performance and exhibited high stability in four successive cycles. The atomic absorption spectroscopy (AAS) experiments performed on the filtrate after each cycle showed a negligible leaching of Nitmtaa from the support N-TUD-1. A plausible reaction mechanism pathway is also proposed.